A strategy for the one-pot direct production of 5-hydroxymethylfurfural (HMF) from sucrose using organic weak acid in situ as a catalyst - Gul, Abdulkadir; Tanyildizi, Muhammet Saban (Elsevier Sci Ltd, 2025)
5-Hydroxymethylfurfural (HMF), which can be produced in high yields by acid-catalyzed dehydration of carbohydrates, is used as a feedstock in biofuel and biopolymer production. However, these acidic catalysts are usually added externally, which increases HMF production costs. Furthermore, other important parameters for high yields of HMF production are raw material selection, reaction medium, and separation-purification processes. The aim of this study is to produce HMF in one-pot without the addition of any exogenous catalyst by evaluating the fructose remaining in the production medium in which the glucose from sucrose hydrolysis is microbially fermented into gluconic acid (GA). HMF production from fructose in a biphasic system consisting of a fermentation liquid containing GA and fructose and 2-Methyltetrahydrofuran (2-MeTHF) was optimized using Central Composite Design (CCD). The variables examined included reaction time, reaction temperature, solvent type, salt type, and organic/aqueous phase ratio. In the study, by chelating GA and calcium ions, the low degree of ionization of GA was increased, and HMF was produced in high yields without the addition of a catalyst. Under optimum conditions, using 2-MeTHF/ fermentation liquid (6:1) and 7.56 wt% CaCl2, the yield of HMF produced in pressurized (hydrothermal) vessels at about 147 degrees C for 158 min reached 77.6 % of the theoretical yield. The amount of GA in the production medium was 92.64 % preserved from degradation. GA and HMF in different phases of the biphasic system were purified from the production medium in high yields. Furthermore, 2-MeTHF, which constitutes the organic phase of the biphasic system, was recovered at approximately 95 % by vacuum evaporation. As a result, HMF production from sucrose, which is a more economical and abundant raw material compared to glucose and fructose, was realized in one-pot without the addition of any catalyst.
Keywords: 5-Hydroxymethylfurfural; Gluconic acid; Biphasic system; Central composite design; One-pot